2009
DOI: 10.1128/aac.01537-08
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Cytochrome P450 2B6 Genotype on Population Pharmacokinetics of Efavirenz in Human Immunodeficiency Virus Patients

Abstract: A population pharmacokinetic model for efavirenz has been developed from therapeutic drug monitoring data in human immunodeficiency virus (HIV)-positive patients by using a nonlinear mixed-effect model. The efavirenz plasma concentrations (n ‫؍‬ 375) of 131 patients were analyzed using high-performance liquid chromatography with UV detection. Pharmacokinetic parameters were estimated according to a one-compartment model. The effects of sex, age, total body weight, height, body mass index, and HIV treatment wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
54
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(64 citation statements)
references
References 46 publications
9
54
0
Order By: Relevance
“…This study complements our previously published report (9) in which we investigated the influence of CYP2B6, CYP3A4, and MDR1 genotypes on EFV kinetics in 32 patients and obtained a final model in which only the effect of the CYP2B6 516G3T polymorphism had an influence on efavirenz clearance; this covariate reduced the intersubject variability of clearance by about 27%.…”
supporting
confidence: 67%
See 3 more Smart Citations
“…This study complements our previously published report (9) in which we investigated the influence of CYP2B6, CYP3A4, and MDR1 genotypes on EFV kinetics in 32 patients and obtained a final model in which only the effect of the CYP2B6 516G3T polymorphism had an influence on efavirenz clearance; this covariate reduced the intersubject variability of clearance by about 27%.…”
supporting
confidence: 67%
“…In particular, the single nucleotide polymorphism (SNP) CYP2B6 516G3T has been reported to be significantly associated with a pronounced reduction in enzyme activity and elevated EFV plasma concen-trations in studies conducted on different populations (1, 9, 11, 15, 20, 24, 31-33, 35, 36, 38, 44, 47, 49, 50, 57). Thus, patients showing G/T and T/T CYP2B6 polymorphisms exhibited EFV clearances that were about 50% and 75% lower than those observed in patients without these polymorphisms (G/G) (9). More recently, the SNPs CYP2B6 983T3G and 785A3G were also reported to affect EFV plasma concentrations (20,21,33,44,49,50,59).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The consideration of a minimum concentration of 1 mg/ liter was based upon an acceptable 70% treatment response rate (15), whereas Stahle and colleagues suggested raising that minimum to achieve at least an 80% response rate (20). Previous studies have shown that patients who had low or subtherapeutic efavirenz concentrations had an increased chance for the development of HIV-resistant strains and subsequent treatment failure (15,21,22). Moreover, efavirenz has a low genetic barrier to resistance; in fact, a single mutation results in high-level resistance to not only efavirenz but also to other drugs in the same class (23).…”
Section: Discussionmentioning
confidence: 99%